2015
DOI: 10.3390/rs70201320
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Optical and SAR Data for Burned Area Mapping in Mediterranean Regions

Abstract: Abstract:The aim of this paper is to investigate how optical and Synthetic Aperture Radar (SAR) data can be combined in an integrated multi-source framework to identify burned areas at the regional scale. The proposed approach is based on the use of fuzzy sets theory and a region-growing algorithm. Landsat TM and (C-band) ENVISAT Advanced Synthetic Aperture Radar (ASAR) images acquired for the year 2003 have been processed to extract burned area maps over Portugal. Pre-post fire SAR backscatter temporal differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
71
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 68 publications
1
71
0
2
Order By: Relevance
“…When pixel number did not reach the 10% of those of the area, the values was not considered (indicated with "n/a" Vaglio for low-biomass forests. Different researches highlighted the usefulness of optical and SAR data for burnt area detection, also used in conjunction in the Mediterranean region (Stroppiana et al 2015). Although optical data have been more frequently used, recent studies have been also conducted with different SAR data types, as shown by the Gitas et al (2012) review.…”
Section: Discussionmentioning
confidence: 99%
“…When pixel number did not reach the 10% of those of the area, the values was not considered (indicated with "n/a" Vaglio for low-biomass forests. Different researches highlighted the usefulness of optical and SAR data for burnt area detection, also used in conjunction in the Mediterranean region (Stroppiana et al 2015). Although optical data have been more frequently used, recent studies have been also conducted with different SAR data types, as shown by the Gitas et al (2012) review.…”
Section: Discussionmentioning
confidence: 99%
“…A binary burned area map (0-unburned, 1-burned) can be derived by applying a threshold to the fuzzy score map [3]. By assessing the accuracy of the burned/unburned area maps as a function of the threshold applied to the fuzzy score map, we found that errors vary between two extremes: a map where areas identified as burned are highly reliable, i.e.…”
Section: Figure 2 Study Area Showing Footprints Of the Considered Opmentioning
confidence: 99%
“…Partial positive and negative evidence brought by the optical and SAR data have been integrated by using Ordered Weighted Averaging (OWA) operators [4,5] and a region growing algorithm has been subsequently applied. For a more detailed description the reader is referred to [3].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations